Some bioclimatic features of wheat growing in Rio Grande do Sul State, Brazil - Pascale, Antonio J.; Mota, Fernando S. da (Pesquisa Agropecuaria Brasileira, 2024)
A joint experiment was carried out through efforts of Faculdade de Agronomia e Veterinária from Buenos Aires, Argentine, and Instituto Agronômico do Sul, Pelotas, Rio Grande do Sul State, in Brazil, to determine bioclimatic requirements of wheat varieties from the South of Brazil. The comparative behaviour of fourtnightly sowing of fifteen varieties was studied in both localities (Buenos Aires and Pelotas) from April to October, 1960, being some varieties of Argentinian wheats, bioclimaticaly well adapted, used as comparative standard according to Geslin's Heliothermic Index. Two groups were established, namely semiprecocious and semilate varieties, and the following characteristics were noted: the vegetative cycle of semiprecocious varieties was accelerated with the upraising of temperature and these varieties showed a manifest insensitiveness to the length of the day, and a certain requirement of cold weather which, though low, must be attended, so that growing may proceed normally. Semilate varieties, on the contrary, require a certain photoperiodicity to form ears, a condition responsible for such late maturation, though not reacting to vernalization, and with growing accelerated by upraising temperatures. To meet the requirements of weather conditions of Rio Grande do Sul State, agroclimatic varieties were studied so as to be used in the wheat farming of that State. Relationship between agroclimatic availabilities and bioclimatic requirements of the varieties used by the farmers concerned was also studied, and a number of effective and optimistic conclusions were attained, to the safeguard of wheat harvests in the South of Brazil.